Penguatan Profesionalisme Guru PAUD melalui Pelatihan Penilaian Perkembangan Anak Usia Dini - Hasbi Hasbi; Sri Jumiaty Permatasari (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2025)
The professionalism of Early Childhood Education (PAUD) teachers is one of the important factors in ensuring the quality of early childhood education. One indicator of this professionalism is the teacher's ability to conduct comprehensive and continuous assessments of child development. However, many PAUD teachers still have difficulty understanding the techniques, instruments, and implementation of child development assessments in accordance with the applicable curriculum. This community service aims to improve the competence of teachers in Anduonohu ​​sub-district in conducting early childhood development assessments through structured training activities. The implementation method for this activity includes the preparation stage, training implementation, and evaluation. The training activities were carried out for two days with a participatory approach that combined interactive lectures, group discussions, case studies, and simulations of the use of assessment formats. The results of the activity showed that the teachers experienced a significant increase in understanding in compiling and using child development assessment instruments, such as anecdotal notes, development checklists, and portfolios. In addition, teachers were able to identify aspects of child development more precisely, and to make systematic records. It can be concluded that this training contributed significantly to strengthening the professionalism of PAUD teachers. In the future, similar training can be expanded to other PAUD institutions with ongoing assistance.